2016
DOI: 10.1186/s40644-016-0092-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capecitabine treatment on the uptake of thymidine analogs using exploratory PET imaging agents: 18F-FAU, 18F-FMAU, and 18F-FLT

Abstract: BackgroundA principal goal for the use of positron emission tomography (PET) in oncology is for real-time evaluation of tumor response to chemotherapy. Given that many contemporary anti-neoplastic agents function by impairing cellular proliferation, it is of interest to develop imaging modalities to monitor these pathways. Here we examined the effect of capecitabine on the uptake of thymidine analogs used with PET: 3’-deoxy-3’-[18F]fluorothymidine (18F-FLT), 1-(2’-deoxy-2’-[18F]fluoro-β-D-arabinofuranosyl) thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Published work in our laboratory and others have demonstrated that successful TS inhibition can result in a compensatory “flare” in thymidine salvage pathway activity that occurs at approximately 2 hrs. following the start of therapy both in vitro[ 1 5 , 19 ] and in vivo[ 3 6 , 20 , 21 ] . This effect was also observed in vivo both in a mouse model of human NSCLC and in a human patient with NSCLC using FLT-PET ([18F]fluorothymidine-positron emission tomography) imaging[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Published work in our laboratory and others have demonstrated that successful TS inhibition can result in a compensatory “flare” in thymidine salvage pathway activity that occurs at approximately 2 hrs. following the start of therapy both in vitro[ 1 5 , 19 ] and in vivo[ 3 6 , 20 , 21 ] . This effect was also observed in vivo both in a mouse model of human NSCLC and in a human patient with NSCLC using FLT-PET ([18F]fluorothymidine-positron emission tomography) imaging[ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic inhibition of thymidylate synthase (TS) is a commonly used strategy in management of a number of malignancies including non-small cell lung cancer (NSCLC). The successful inhibition with commonly used therapeutics, 5-FU[ 1 3 ], pemetrexed[ 4 , 5 ] and capecitabine[ 6 ] have all been demonstrated to induce a transient burst of compensatory activity through the thymidine kinase pathway within hours of exposure to the chemotherapeutic. This transient burst in thymidine salvage pathway activity is measureable with FLT-PET ([18F]fluorothymidine -position emission tomography)[ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, this drug-induced compensatory “flare” in thymidine salvage pathway activity is an indicator of successful TS inhibition. This drug-induced change in tumor metabolism can be made visible through 18 F-thymidine (FLT)-positron emission tomography (PET)[ 2 , 5 7 ], an analog of thymidine. FLT, first described by Shields in 1998 [ 8 ], is an investigational imaging biomarker of the thymidine salvage pathway currently in use for human clinical trials primarily as a validated surrogate marker of tumor proliferation [ 9 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the absence of tumoural FLT flare with gemcitabine unlike fluoropyrimdines, in preclinical models has been attributed to the competition in tumoural uptake between FLT and gemcitabine, both of which use the same nucleoside transporter, hENT1. It is difficult to delineate if the decreased uptake in tumour and normal tissues in this subject is a true representation of decreased proliferative activity, or as a result of competition between gemcitabine and FLT for transport in to tissue [23,37]. No relationship between the imaging and pathologic parameters were identified.…”
Section: Discussionmentioning
confidence: 96%